Application of strontium isotope analysis to provenance studies of Early Bronze Age North-Mesopotamian Metallic Ware. (December 2017) - Kibaroğlu, Mustafa; Falb, Christian; Hartmann, Gerald
Abstract: Sr isotopic analysis was carried out on Early Bronze Age ( c . 2800–2200 BCE) North-Mesopotamian Metallic Ware and clay samples collected from south-eastern Anatolia and north-eastern Syria with a view to determining the provenance of this characteristic ceramic type, in particular of its non-calcareous variant. The non-calcareous and calcareous variants of North-Mesopotamian Metallic Ware, which have been defined in previous archaeometric studies, show a clear distinction in their Sr isotopic signatures. The non-calcareous group is characterised by high 87 Sr/ 86 Sr ratios, whereas the calcareous variant has much lower values. The Sr isotopic signature of the non-calcareous group shows similarities with clay samples from the Pütürge Massif area in south-east Anatolia. Combining the results of the present study with previous investigations, it is thought that the raw material used for the production of non-calcareous North-Mesopotamian Metallic Ware could have been originated from the southern part of the Pütürge Massif area. Furthermore, this study proves that Sr isotope analysis is a useful tool for the characterisation and identification of archaeological ceramic provenance.